Pulmonary Atresia with Intact Ventricular Septum in a Neonate - Yonas, Emir; Pranata, Raymond; Nusarintowati, Nuvi (The Indonesian Heart Association, 2017)
Introduction: Pulmonary atresia with an intact ventricular septum is a condition that is characterized by a complete obstruction to right ventricular outflow with varying degrees of right ventricular and tricuspid valve hypoplasia. This condition is uniformly fatal if untreated. In this case report, we present a case of a neonate with a pulmonary atresia with intact ventricular septum Case Presentation: A 2 days-old female Indonesian newborn was referred to our facility. The newborn was delivered from a G4P3A0 mother with a gestational age of 39 weeks (term delivery). Chest x-ray done at the referring facility is significant for a seemingly right heart hypertrophy, casting a “boot-shaped” appearance of the right heart border. Laboratory results done at the referring facility is significant for a neutrophilia of 82% and lymphocytopenia of 13% An episode of hypoglycemia was reported on referring facility with a blood sugar level of 50 mg/dl. Multiple episodes of cyanosis were reported at referring facility, CPAP was administered but the improvement was limited. Pulse oximetry averaged between 72-80% at the referring facility. Physical examination shows an actively moving neonate, with a strong cry. Perioral cyanosis was seen. Vital signs were as follows; heart rate 128 x / minute, temperature 37oC, respiratory rate 54 x / minute, pulse oximetry 74%, capillary refill time < 3 seconds. The rest of the physical examination was within normal limits. Laboratory result on admission at our facility is significant for low hematocrit, low erythrocyte count, leukopenia with neutrophilia and thrombocytopenia. Patient was admitted to NICU and given CPAP. Echocardiography 2 days upon arrival at our facility reveals a patent ductus arteriosus with the pressure of 4-5 mmHg and diameter of 0.3 cm, no forward flow from the right ventricle to the pulmonary artery, doppler mode demonstrated pulmonary artery filling from ductus arteriosus. The rest of the findings were within normal limits. Conclusion: Pulmonary atresia with an intact ventricular septum is a condition that relies on the patent ductus arteriosus for pulmonary blood supply, the patency of it is of paramount importance.   Abstrak PENDAHULUAN: Atresia arteri pulmonalis dengan septum ventrikel yang utuh merupakan kondisi yang dikarakterisasikan dengan sumbatan total pada right ventricular outflow dengan berat hipoplasia ventrikel kanan dan trikuspid kanan yang beratnya bervariasi. Pada umumnya kondisi tersebut fatal apabila tidak ditangani. Pada laporan kasus ini, kami melaporkan suatu kasus neonates dengan atresia arteri pulmonalis dengan septum ventrikel yang utuh. PRESENTASI KASUS: Neonatus perempuan berumur 2 hari dirujuk ke rumah sakit kami. Bayi dilahirkan dari G4P3A0 usia kehamilan 39 minggu. Ronsen thoraks yang dilakukan oleh fasilitas kesehatan yang merujuk memperlihatkan hipertrofi jantung kanan serta bentuk “boot-shaped” pada batas jantung kanan. Hasil laboratorium pada fasilitas kesehatan tersebut menunjukan neutrofilia dan limfositopenia. Terdapat juga riwayat hipoglikemi. Episode sianosis berulang terjadi pada fasilitas kesehatan yang merujuk. Pemasangan CPAP kurang membuahkan hasil dengan saturasi O2 72-80% ketika tiba pada rumah sakit kami. Pemeriksaan fisik menunjukan tangis kuat dan gerak aktif dengan sianosis perioral. Detak jantung 128 kali/menit, suhu 37oC, laju naas 54 kali/menit, oksimetri nadi 74% dan waktu isi kapiler <3 detik. Pemeriksaan laboratorium saat pasien dating menunjukan hematocrit, hitung eritrosit, leukosit dan thrombosit yang rendah. Pasien dirawat di NICU dan diberikan CPAP. Ekokardiografi 2 hari kemudian menunjukan duktus arteriosus patent dengan tekanan 4-5 mmHg dan diameter 0.3 cm, tidak ada aliran maju dari ventrikel kanan kepada arteri pulmonalis, mode Doppler menunjukan pengisian arteri pulmonalis dari duktus arteriosus. Pemeriksaan lainnya dalam batas normal. KESIMPULAN: Atresia arteri pulmonalis dengan septum ventrikel yang utuh merupakan suatu kondisi dimana aliran darah menuju paru bergantung pada duktus arteriosus yang paten sehingga patensi daripada duktus tersebut sangatlah penting